The effectiveness of promotional activities carried out by higher and Tertiary institutions on students’ choice of university - Ngwenya, Stanley (Midlands State University, 2017)
The study sought to assess the effectiveness of promotional activities carried out by Higher and Tertiary Institutions on students’ choice of university since higher and tertiary institutions have adopted promotional tools to attract more students to survive competition hence the need to examine the effectiveness of these activities being undertaken. Literature reviewed identified Advertising, PR and publicity, direct marketing methods, sponsorships, sales promotion and exhibitions as main elements of the promotional mix. However some scholars argue that publicity cannot be included in the promotional mix. Exploratory research design was used to acquire preliminary data while descriptive research design allowed the researcher to obtain data quantitatively and qualitatively using questionnaires and interviews as research instruments. A sample size of 90 respondents was used. Research findings indicated that students who came to know about MSU through the newspaper were 24.69%, and word of mouth had 33.33% open days 11.11%. Of the respondents 53.09% strongly agreed that MSU has a good reputation. Those who had been exposed to MSU’s exhibition were 75.35% and 46 % of these rated the exhibitions as effective. Lastly the research findings showed that 9.88% strongly agreed that location has influence on university attraction whilst 56.79% agreed. In this regard the research concluded that newspaper advertising is an effective vehicle of promotion to expose prospective students MSU. Newspapers target the mass and commands wide readership. Exhibitions exposed a higher percentage of the respondents (75.35%) to MSU’s brand indicating that these exhibitions are effective. Furthermore PR activities being undertaken by MSU are effective since university’s image is able to attract students even from other countries. Lastly the research concluded that Location has influence on university attractiveness. It is in this view that the researcher recommends the university to improve the current communication strategies and PR as they were indicated to be effective by respondents. Suggestions are made to the university resume career guidance programmes since results shows that it has positive influence on students’ choice of university. The University may also advertise in more different papers to include the chronicle which is popular in Matebeland province as to capture wide coverage and readership in the region. University may set up some ways to measure the effectiveness of the newspaper adverts on students’ choice. The university may make some efforts to attend more exhibitions especially provincial agricultural shows so that they have visibility in other provinces other than Harare, Matebeleland and Midlands Province.